2019
DOI: 10.3390/ijms20164020
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of the T790M and L858R Mutations in the EGFR Gene by Oligoribonucleotide Interference-PCR

Abstract: A de novo single-nucleotide mutation in the EGFR gene can cause the development of lung cancer. EGFR tyrosine kinase inhibitors (EGFR-TKIs) are used for clinical treatment of such lung cancers, but acquired resistance often mitigates their efficacy. Accordingly, monitoring of de novo and acquired nucleotide mutations is essential for clinical treatment of lung cancers with EGFR-TKIs. Previously, we reported that oligoribonucleotide interference-PCR (ORNi-PCR) can accurately and cost-effectively detect single-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…3A and B; Supplementary Table S1 ). Because we previously confirmed that wild-type EGFR mRNA is expressed in various lung cells, such as a normal lung fibroblast cell line, MRC-5, and a nonsmall cell lung carcinoma cell line, NCI-H1299 [ 11 ], total RNA was extracted from MRC-5 and used as a model RNA. RT reactions were performed using total RNA and the oligo(dT) primer in the presence of the dCas13a/gRNA_EGFR RNP complex, the dCas13a protein alone, or the gRNA alone.…”
Section: Resultsmentioning
confidence: 99%
“…3A and B; Supplementary Table S1 ). Because we previously confirmed that wild-type EGFR mRNA is expressed in various lung cells, such as a normal lung fibroblast cell line, MRC-5, and a nonsmall cell lung carcinoma cell line, NCI-H1299 [ 11 ], total RNA was extracted from MRC-5 and used as a model RNA. RT reactions were performed using total RNA and the oligo(dT) primer in the presence of the dCas13a/gRNA_EGFR RNP complex, the dCas13a protein alone, or the gRNA alone.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular targeted therapy shows advantages for many diseases, especially malignancies (Baba et al, 2019;Becker et al, 2020;Xu P. et al, 2020). LncRNAs contribute to disease progression through the regulation of cellular pathways (Li Z.-W. et al, 2020;Sun and Wu, 2020).…”
Section: Linc00346 As a Biomarker Of Targeted Therapymentioning
confidence: 99%
“…Previously, we developed an oligoribonucleotide (ORN)-mediated blocking PCR named ORN interference-PCR (ORNi-PCR) (Figure A) . ORNi-PCR clearly discriminates nucleotide differences such as indel mutations (which are introduced by genome editing events), single-nucleotide mutations in cancer cells, and nucleotide polymorphisms. In general, DNA polymerases lacking 5′–3′ exonuclease activity are used for ORNi-PCR because those retaining the 5′–3′ exonuclease activity, such as Taq DNA polymerase, can remove a hybridized ORN during DNA extension. In fact, we observed that DNA amplification by Taq DNA polymerase is not inhibited by an ORN .…”
Section: Introductionmentioning
confidence: 99%